Resistance to antibody‐drug conjugates in breast cancer: mechanisms and solutions - Yu‐Fei Chen; Ying‐ying Xu; Zhi‐Ming Shao; Ke‐Da Yu (Cancer Communications, 2023)
Abstract Antibody‐drug conjugates (ADCs) are a rapidly developing therapeutic approach in cancer treatment that has shown remarkable activity in breast cancer. Currently, there are two ADCs approved for the treatment of human epidermal growth factor receptor 2‐positive breast cancer, one for triple‐negative breast cancer, and multiple investigational ADCs in clinical trials. However, drug resistance has been noticed in clinical use, especially in trastuzumab emtansine. Here, the mechanisms of ADC resistance are summarized into four categories: antibody‐mediated resistance, impaired drug trafficking, disrupted lysosomal function, and payload‐related resistance. To overcome or prevent resistance to ADCs, innovative development strategies and combination therapy options are being investigated. Analyzing predictive biomarkers for optimal therapy selection may also help to prevent drug resistance.